Case Report: Deep Brain Stimulation of the Nucleus Basalis of Meynert for Advanced Alzheimer's Disease - Zhang, Wei; Liu, Wei; Patel, Bhavana; Chen, Yingchuan; Wang, Kailiang; Yang, Anchao; Meng, Fangang; Wagle Shukla, Aparna; Cen, Shanshan; Yu, John; Ramirez-Zamora, Adolfo; Zhang, Jianguo (Frontiers in Human Neuroscience, 2021)
Patients with advanced Alzheimer’s disease (AD) experience cognitive impairment and physical disabilities in daily life. Currently, there are no treatments available to slow down the course of the disease, and limited treatments exist only to treat symptoms. However, deep brain stimulation of the nucleus basalis of Meynert (NBM-DBS) has been reported to improve cognitive function in individuals with AD. Here, we report the effects of NBM-DBS on cognitive function in a subject with severe AD. An 80-year-old male with severe AD (Clinical Dementia Rating scale: 3.0 points) underwent surgery for bilateral NBM-DBS electrode placement. After ten weeks of stimulation, Mini-Mental State Examination (MMSE) assessment improved from a score of 5 to 9 points, and assessment using the Alzheimer’s Disease Assessment Scale-Cognitive (ADAS-cog) scale showed a marked reduction in total score from 43 to 33 points, suggesting cognitive benefits from NBM-DBS. The patient's post-operative course was complicated by a subdural effusion which occurred several days after surgery, with complete recovery. Interestingly, the subject also displayed abnormal thermoregulation with stimulation initiation and stimulation parameter modifications. NBM-DBS may serve as a potential therapy for severe AD patients.